Evaluation of the Implementation of the Puskesmas Management Information System (SIMPUS) on Primary Health Care Efficiency - Khaeriah B; Antik Pujihastuti; Gede Wirabuana Putra (Miracle Journal Get Press, 2025)
The implementation of health information systems is crucial to enhancing efficiency in primary health care centers, yet systems like the Puskesmas Management Information System (SIMPUS) are not fully optimized in many Indonesian health centers. Ideally, SIMPUS should enable faster, more accurate, and integrated services, but inefficiencies persist. This study evaluated SIMPUS implementation and its effect on service efficiency in several Puskesmas in Padang City, Indonesia. A cross-sectional descriptive quantitative study was conducted using a structured questionnaire based on the Human-Organization-Technology Fit (HOT-Fit) framework and the Technology Acceptance Model (TAM). Eighty health workers with varying roles and SIMPUS usage experience participated. Descriptive statistics assessed respondent characteristics and perceptions of service effectiveness. Results showed that among 40 respondents, 37 (92.5%) who rated SIMPUS highly (score >4.0) also reported high satisfaction with service effectiveness. Chi-Square and simple linear regression analyses found a significant relationship between system perception and service efficiency. Higher perceived efficiency was noted among users with over two years of experience, administrative and medical record staff, and female health workers. These findings highlight the gap between SIMPUS’s potential and actual outcomes, emphasizing the need for technological readiness, continuous training, system updates, and committed leadership to advance digital transformation in primary health care.